2014
DOI: 10.1016/j.msea.2014.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mechanical properties in SUS304L steel through the control of bimodal microstructure characteristics

Abstract: The present work deals with achieving improvement in the mechanical properties of SUS304L stainless steel through the application of a unique microstructure design termed as 'Harmonic structure', and establishing a co-relationship between various microstructural characteristics and mechanical properties. Harmonic structure essentially means a bimodal grain size distribution with a specific periodic arrangement of coarse-and ultrafine-grain fractions. SUS304L stainless steel samples having such microstructure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 213 publications
(87 citation statements)
references
References 35 publications
(47 reference statements)
5
82
0
Order By: Relevance
“…It appears that the plastic deformation is only limited to the surface of the powder particles. Similar morphological observations have been reported also in literature 9,12,13) . Moreover, it is also noticed that the Si particles have fragmented to signi cantly smaller particle size after mechanical milling.…”
Section: Methodssupporting
confidence: 92%
See 2 more Smart Citations
“…It appears that the plastic deformation is only limited to the surface of the powder particles. Similar morphological observations have been reported also in literature 9,12,13) . Moreover, it is also noticed that the Si particles have fragmented to signi cantly smaller particle size after mechanical milling.…”
Section: Methodssupporting
confidence: 92%
“…Recently, Ameyama and co-workers have proposed a microstructural design to improve mechanical properties by obtaining both high strength and high ductility in metallic materials, through the formation of so-called harmonic structured material [1][2][3][4][5][6][7][8][9][10][11][12][13] . Essentially, it is an exquisite heterogeneous microstructural design, consisting of bimodal grain size distribution, in which ductile coarse grained regions (termed as core ) are enclosed in a continuously connected three-dimensional networks regions with high strength ultra-ne grained structure, known as shell .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with the above-mentioned issues of controlled heterogeneous microstructure, Ameyama et al proposed an integrated approach to prepare bulk materials with a controlled and unique heterogeneous microstructure, called 'harmonic structure' (HS), with bimodal grain size distribution. [15][16][17][18][19][20][21][22][23][24][25] A schematic diagram illustrating the HS design is shown in Figure 1. The HS is a heterogeneous microstructure with a specific spatial distribution of fine and coarse grains, that is, the CG areas ('core') embedded in the matrix of three-dimensional continuously connected network ('shell') of fine-grained (FG) areas.…”
mentioning
confidence: 99%
“…It has also been demonstrated that the shell/core fraction can be successfully controlled by controlling milling time and number of milling passes in BM process and JM process, respectively. [19][20][21][22] The milled bimodal powders are consolidated at elevated temperatures to prepare bulk materials. Recently, spark plasma sintering (SPS) has been used extensively for the consolidation due to rapid sintering together with avoidance of deformation induced texture during consolidation process.…”
mentioning
confidence: 99%